(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The present study was employed to investigate the abilities of leaves extract of Morus nigra to alleviate the oxidative stress and histopathological changes associated with induced diabetes mellitus of adult males wistar. rats. The present study was included 24 male rats with average age of 5 weeks and 150-210 g weight were used classified into four groups and each group included six (6) male rats. The first group was used as a control group and administered normal diet. The second group was injected intraperitoneally (IP) with alloxan 120mg/kg for 3days. The third group was also injected IP with alloxan 120mg/kg and administered orally with leaves extract of Morus nigra (500mg) for six weeks. Finally, the fourth group was administered with leave extract of Morus nigra (500mg) orally for six weeks. At the end of experiment blood samples were taken and the blood serum was separated by centrifuge to measure glucose concentration and anti-oxidant level (superoxide dismutase (SOD) levels) than the animals were sacrificed and liver was taken for changes of the hepatic tissues study.The results obtained from this study indicated that the extract of Morus nigra has ability to increase anti-oxidant activity significantly (p<0.05) in affected animals when compared with non-treated affected animals. The result of glucose showed significant decrease(p<0.05) in affected animals when compared with non-treated affected animals.Concerning histopathological changes of liver the result showed improvement of pathological changes of the hepatic tissues of affected animals receiving leave extract of Morus nigra in a comparison with other tested groups.